P205 Admission trends and outcomes of individuals with bronchiectasis admitted to adult general critical care units in England, Wales and Northern Ireland. (12th November 2015) - Navaratnam, V; Muirhead, C; Hubbard, RB; De Soyza, A
Abstract : Introduction: Whilst studies suggest increasing incidence and mortality from bronchiectasis in UK, there are sparse data on outcomes of individuals with bronchiectasis admitted to intensive care (ICU). We investigated trends in bronchiectasis admissions to ICU and estimated outcomes in patients with bronchiectasis admitted to ICU compared to a better studied group, i.e. Chronic Obstructive Pulmonary Disease (COPD). Methods: We used data from the Intensive Care National Audit and Research Centre (ICNARC), a database of patient outcomes from adult critical care units across England, Wales and Northern Ireland. 95% of adult critical care units contribute data to ICNARC which includes information from 1.5 million individuals. Admissions from bronchiectasis and COPD from 1/1/2009 to 31/12/2013 were extracted. Bronchiectasis admissions included patients whose primary or secondary reason for admission was exacerbation of bronchiectasis, excluding people with cystic fibrosis. COPD admissions were those whose primary or secondary reason for admission was either COPD with acute lower respiratory infection; or COPD with acute exacerbation. Patients with COPD-bronchiectasis overlap were excluded. ICU mortality was defined as status on leaving ICU. Results: There were 614, 352 admissions across 219 critical care units during the study period, 536 (0.1%) of which were from bronchiectasis and 19, 754 (3.2%) from COPD. Bronchiectasis admissions increased from 74 in 2009 to 121 in 2013, equating to a crude annual increase of 8% (95% Confidence Interval [CI] 2 to 15%; p = 0.01) (see Table 1 ). The mean age increased from 56.6 (standard deviation [SD] 18) to 65.8 years (SD 15.2; p = 0.042) whilst ICU mortality did not change (27.0% vs 28.9%; p = 0.83). The unadjusted yearly increase in COPD admissions was 1% (95% CI: 0.3% to 2%; p = 0.012). The mean age in COPD patients remained static (67.5 years [SD 10.6] vs. 67.9 years [SD 10.6]; p = 0.16), but ICU mortality decreased (20.5% vs. 18.0%; p = 0.005). ICU mortality in people with bronchiectasis over 70 (n = 219) was higher compared to those under 70 (31.1% vs. 18.3%; p < 0.001) despite having similar mean APACHE II acute physiology scores. Conclusion: Bronchiectasis admissions to ICU are increasing, and ICU mortality for is higher bronchiectasis compared to COPD, particularly in individuals above 70 years of age.